An Empirical Study on the Role of Parents in Academic Achievement of Children in Private Schools of Karachi - Muhammad Yaseen, Muhammad Yaseen; Zaman, Shah; Rasheed, Naveeda (International Journal of Criminology and Sociology, 2017)
This study examines the parental involvement in the academic achievement of the children in Old Golimar, Karachi. The factors included in the study were parental involvement which is measured with; communicating of parents, decision making of parents, friendly behavior of parents, qualification of parents, parents’ schools’ association, parent child interaction, parent teachers’ meetings, to understand the children, solving children problems, helping the children in school works and academic achievement which is measured with; response of children, potential of children, hesitation of children, outcome of children, academic performance, good marks, participation in activities, school work completion, good attendance, being active in class, understanding the lecture and over all factors of parental involvement in the academic performances of the children in Old Golimar, Karachi. After getting the list of total enrollments of schools then the researcher used Raosoft sample size calculator, and got the sample of 165 out of total population, which was 714. Proportionate stratified sampling technique was used and data collected through a structured questionnaire. The results and findings of the whole research show that there is a significant relationship between the parental involvement and the academic achievement of the children.This study examines the parental involvement in the academic achievement of the children in Old Golimar, Karachi. The factors included in the study were parental involvement which is measured with; communicating of parents, decision making of parents, friendly behavior of parents, qualification of parents, parents’ schools’ association, parent child interaction, parent teachers’ meetings, to understand the children, solving children problems, helping the children in school works and academic achievement which is measured with; response of children, potential of children, hesitation of children, outcome of children, academic performance, good marks, participation in activities, school work completion, good attendance, being active in class, understanding the lecture and over all factors of parental involvement in the academic performances of the children in Old Golimar, Karachi. After getting the list of total enrollments of schools then the researcher used Raosoft sample size calculator, and got the sample of 165 out of total population, which was 714. Proportionate stratified sampling technique was used and data collected through a structured questionnaire. The results and findings of the whole research show that there is a significant relationship between the parental involvement and the academic achievement of the children.